The Trouble With Tebowing. (May 2014) - Yukich, Grace; Stokes, Kimberly; Bellows, Daniela
Sociologists Grace Yukich, Kimberly Stokes, and Daniela Bellows explore cultural norms around religious displays in sports, and in public life more generally, by examining media coverage of controversial football player Tim Tebow.